ڕۆژنامەى پێشکەوتن 1920 – 1922 و کاریگەرى لە بزوتنەوەى ئەدەبیدا - محمد, محەمەد دلێر ئەمین (Sulaimani Journal for Humanities, 2003)
Peshkewtin newspaper is the first Kurdish newspape to be published in Sulaimani from April 29th, 1920 to July 27th, 1922. - Though this newspaper was published by the order of the British political authority, which was basically motivated by politics and information in the history of Kurdish journalism objectives. This newspaper is unique in that it issued 118 copies. This newspaper has offered a lot of services to Kurdish literature and cultural movement in Sulaimani and its outskirts. It has been a motivation to Kurdish prose art, social discourse, political and economic writings. It has changed the Kurdish language from spoken language to written language. It has introduced the profession of journalism to the area and has encouraged many poets and writers of that time to be busy with journalism career as well to serve Kurdish contemporary literature. This study deals with those aspects of literature and journalism which for the first time in a brief study and such a kind of newspaper introduce the significance and value of this newspaper at the time.